CHRISTUS SALVATOR: God’s Salvation in Christ, Christ’s Finality, and the Christian Mission within a Religiously Pluralistic World - Oppong-Konadu, Kwame (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2024)
Considering the many diverse religious traditions coexisting in the same societies across the globe, the issue of how Christianity relates to other religions has become increasingly important. Theologians have developed three main approaches that address this issue: exclusivism, inclusivism, and religious pluralism. This article offers a critical examination of these approaches using a literature study. It also delves into the truth claim about Christ’s finality and salvific role in the world, exploring its implications for Christian missions. It argues that while adhering to Christ’s finality in the religiously pluralistic world is still relevant for contemporary Christians, it is necessary to engage respectfully and sensitively when approaching missions among people of other faiths. The article advocates a P-H-D model for missions, demonstrating the significance of three missional attitudes: Perseverance, Humility, and Dialogue.